Penerapan Sistem Pembayaran Qris dan Pendaftaran Google Maps Sebagai Upaya Meningkatkan Akses dan Daya Saing UMKM di Kelurahan Harjosari - Fajriani Ananda; Laura Mairenza Efendes; Gratiana Br Manik (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out with the primary objective of improving digital literacy and the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Harjosari Village through the implementation of a Quick Response Code Indonesian Standard (QRIS)-based payment system and business location registration on Google Maps. This digital transformation is expected to address the challenges faced by MSMEs amidst technological developments and increasingly fierce market competition. The activity implementation method includes several stages. First, identification of MSME needs and conditions is carried out through interviews and observations to understand the level of digital literacy and readiness to adopt technology. Second, socialization is provided to introduce the benefits of QRIS and Google Maps, while also building awareness of the importance of a digital presence for businesses. Third, technical training focused on how to create an account, activate QRIS, and register a business location on Google Maps. Fourth, direct mentoring is provided to ensure that MSMEs can apply these new skills independently in their daily business activities. The results of the activity show a significant increase in transaction efficiency, as QRIS enables a fast, secure, and cash-free payment process. Business registration on Google Maps also increases business visibility online, making it easier for potential customers to find business locations and information. Furthermore, business owners' confidence in using digital technology has increased, which in turn expands market opportunities. However, challenges remain, such as resistance from some MSMEs to QRIS transaction fees and limited digital literacy among certain groups. Overall, however, this activity provides concrete evidence that digital transformation through QRIS adoption and optimizing online presence can strengthen MSMEs' position in the digital economy era, while simultaneously opening up opportunities for business sustainability and growth.